Drymaria veliziae (Caryophyllaceae), a new species from the Andes of Cajamarca (North Peru). - Montesinos-Tubée, D.B. (2020)
A new species from the Northern Peruvian Andes (Cajamarca department), Drymaria veliziae sp. nov., is proposed in the present paper. It grows in the high-elevation montane grasslands and it is morphologically similar to D. auriculipetala from which it differs in having elliptic-ovate leaves, blade margin bases glandular, large number of stipules arranged in a pedicel form at the leaf axis and by the short and glandular pedicels. A detailed description, original photographs and a location map are provided, as well as an updated diagnostic key of Drymaria Ser. Frutescens. The IUCN status of the new species is assessed as Endangered (EN).